Report of the South Commission : implications for Latin America and the Caribbean (SELA CaracasVE, 1991)
Presents the broad focus of the Commission's report, examines specific problems facing the South and evaluates the report. Discusses the broad implications of the study for Latin America and the Caribbean and selects a number of policy areas contained in the report which are of special relevance to the region.
DC